Emergent Transcriptomic Technologies and Their Role in the Discovery of Biomarkers of Liver Transplant Tolerance - Mastoridis, Sotiris; Martínez-Llordella, Marc; Sanchez-Fueyo, Alberto (Frontiers in Immunology, 2015)
Liver transplantation offers a unique window into transplant immunology due, in part, to the considerable proportion of recipients who develop immunological tolerance to their allograft. Biomarkers able to identify and predict such a state of tolerance, and thereby able to establish suitable candidates for the minimisation of hazardous immunosuppressive therapies, are not only of great potential clinical benefit, but might also shed light on the immunological mechanisms underlying tolerance and rejection. Here we review the emergent transcriptomic technologies serving as drivers of biomarker discovery, we appraise efforts to identify a molecular signature of liver allograft tolerance, and we consider the implications of this work on the mechanistic understanding of immunological tolerance.